Prespektif Geografi Kajian Geografi Manusia: Dinamika Kebudayaan dan Identitas Sosial dalam Konteks Globalisasi - Triyatno, Wigit; Ifana Sari, Yuli (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to explore the relationship between human geography, culture and social identity in the context of globalization and will examine geographical factors. Cultural exchanges, migration flows, and the penetration of information technology have accelerated intercultural integration but have also created new challenges in maintaining local identity. The research method applied in this article involves literature study or literature analysis.This research involves techniques such as studying related literature, summarizing data, sorting data, and concluding the results. Through data analysis and field findings, it shows that geographical factors such as location, physical environment and social structure have a significant impact in shaping and changing culture and human social identity, globalization has become the dominant factor that shapes the dynamics of culture and social identity throughout the world. world. Globalization, as a process of global economic, social and cultural integration, has produced various complex impacts on human life. This research provides new insights in understanding social and cultural dynamics in the era of globalization. By understanding how human geography influences cultural interactions and the formation of social identities, policies can be designed that are more effective in managing cultural diversity and promoting inclusive social development. Â